ECONOMIC AND INSTITUTIONAL FUNDAMENTALS OF THE DIVERGENCE OF DEVELOPMENT PATHS IN CENTRAL AND EASTERN EUROPE - Bilenko, Yuriy (Ekonomika, 2013)
Abstract. An analysis of the divergence of economic development paths of Eastern European countries (Poland, Hungary, Latvia, Lithuania, Czech Republic, Slovakia, Slovenia) that joined the EU in 2004 and of the European post-Soviet states (Ukraine, Russia, Belarus, Moldova) for the past twenty years with an emphasis on trade and financial openness is carried out in the article. A detailed description of institutional mechanisms and institutional changes in the economies of these two groups of countries is presented. In my opinion, in order to ensure a sustainable economic development and sustainable economic growth, the macroeconomic equilibrium has to be supplemented by the institutional equilibrium. The equilibrium criteria have to match the actual functions of the institutions, assigned to them by society, and contribute to the development of the whole society along with formation of the middle class.Key words: economic development, economic growth, institutional change, transition economy, Central and Eastern Europe